2020
DOI: 10.33483/jfpau.754110
|View full text |Cite
|
Sign up to set email alerts
|

A Questionnaire-Based Study on Medicinal Plant Use in Respiratory Diseases

Abstract: Objective: We aimed to investigate the rates of medicinal plant use, species of medicinal plants, detailed usage and procurement information, the sociodemographic features affecting the tendency to use plants and the notification status to healthcare professionals in patients with respiratory diseases. Material and Method: This study was carried out between January-April 2018 at the Molla Gurani Family Healthcare Center. An 18-item survey questionnaire was administered to patients suffered from respiratory dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
1
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
1
1
0
1
Order By: Relevance
“…We also reported that most participants (66.5%) considered the safety of the herbal remedies before get them and purchased herbal remedies at a monthly cost of between 51-100 (38.6%). In this study as well as in our previous study a large majority of participants declared that herbal remedies are beneficial and recommended the medicinal plants to other people [24]. On the other hand, Alyami et al [21] reported that most respondents in Saudi Arabia thought that vitamins and herbal supplements can not treat/reduce the incidence of Covid-19.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…We also reported that most participants (66.5%) considered the safety of the herbal remedies before get them and purchased herbal remedies at a monthly cost of between 51-100 (38.6%). In this study as well as in our previous study a large majority of participants declared that herbal remedies are beneficial and recommended the medicinal plants to other people [24]. On the other hand, Alyami et al [21] reported that most respondents in Saudi Arabia thought that vitamins and herbal supplements can not treat/reduce the incidence of Covid-19.…”
Section: Discussionsupporting
confidence: 61%
“…More than half (53.4%) of the herbal remedy users stated that they used herbal remedies a few days a week. In our previous study on patients with respiratory diseases, we reported that participants obtained medicinal plants from their friends and relatives [24]. In Nepal and Saudi Arabia, most of the people provided medicinal plants from their own home, home gardens or farms [21,23].…”
Section: Discussionmentioning
confidence: 99%
“…solunum yolu hastalığı olan bireylerle yaptıkları çalışmada, katılımcıların %64,5'inin hastalıklarının tedavisi için tıbbi bitkiler kullandığını belirlemiştir. 9 Bu sonuçlar, bireylerin TAB kullanımı konusunda yeterli bilgiye sahip olmadığını düşündürmektedir. Ülkemizde TAB kullanımına yönelik bilinç henüz yeterli düzeyde değildir.…”
Section: Discussionunclassified